Protecting parents, idealizing the past, blaming friends: life stories of men imprisoned for violence - Agoff, Carolina (International journal of offender therapy and comparative criminology, 2025)
Life-stories emerge from a wide variety of facts and events in individual lives and weave a selected few of these together to make meaning in the present. They are crucial for constructing identity and influence action by establishing worldviews and a persona that narrators will seek to confirm. In this study we describe three main themes in the life-stories of six incarcerated men in Argentina: a) Protecting family, especially parents; b) reconstructing an ideal past, and contrasting it with a more cynical present; and c) blaming criminal neighborhoods, friends, and girlfriends for their crimes. We discuss how these themes are intertwined, what function they fulfill, and the identities and masculinities they produce. Combining research on life-stories with narrative and psychosocial criminology the analysis reveals how life-stories of incarcerated men can be seen as attempts at countering stigma and defending a self that is under attack. The life-stories portray a believable, ‘good’, and multifaceted image of the self, but most importantly, create coherence and unity in otherwise chaotic lives.